Analysis of Vegetation’s Ability to Reduce Noise in Udayana Urban Forest - Rahmawati, Yeni; B, Kornelia Webliana; Wulandari, Febriana Tri (Jurnal Biologi Tropis, 2024)
Mataram City, the capital city of West Nusa Tenggara Province, is experiencing rapid development which has an impact on increasing noise in urban areas. This study aims to analyze the ability of vegetation to reduce noise in the Udayana Urban Forest. This study uses a quantitative descriptive method, with location selection using purposive sampling. Noise reduction measurements using a Sound Level Meter at four observation points with variations in canopy cover and the distance variable of vegetation from the noise source. This study shows that vegetation has an essential role in reducing noise, with a noise level reduction value in the open dominance area of ​​the eastern area of ​​8.2 dBA and the western area of ​​8.7 dBA. At a sparse vegetation density level, a decrease of 6 dBA in the western and eastern areas is constant. At a moderate vegetation density level, a decrease of 4.5 dBA in the western and eastern areas, the noise value is constant. In vegetation with high/dense density, there was a decrease of 5.9 dBA in the eastern and western areas of ​​7.1 dBA. Based on the distance variable, noise reduction in the open dominance area decreased by 6.1 dBA in the eastern area and 6.7 dBA in the western area. In areas with sparse vegetation density, there was a decrease of 6.8 dBA in the East and 6 6.0 dBA in the West. For moderate vegetation density, there was a decrease of 6.4 dBA in the East and 6.1 dBA in the West. In areas with high/dense vegetation density, there was a decrease of 3.6 dBA in the East and 4.4 dBA in the West. The regression analysis results showed that canopy cover and distance significantly affected noise levels with a strong relationship, where the denser the canopy cover and the farther the distance, the noise level would decrease.